Analysis of two different approaches to the design of industrial lighting equipment - Yevhenii Lobanov; Olena Didenko; Glib Petchenko (O.M. Beketov National University of Urban Economy in Kharkiv, 2025)
This paper examines two approaches that are relevant today in the design of industrial lighting fixtures. The first concerns the development of new modifications of traditional fixtures with discharge lamps. The authors considered the methodology proposed by the authors for calculating the profile of a specular reflector, which, together with a selected light source of fixed type and power, forms an optical system of the device that provides regulated light distribution of the luminaire as a whole. The method allows you to quickly and effectively obtain the necessary simple and technologically oriented designs of mirror reflectors for lamps, is amenable to automation and is flexible when switching from one type of discharge lamps to another, taking into account different types of their power. The second approach is focused on the use of LED modules, which are created specifically for industrial lighting tasks and are available for production and sale. A feature of designing an LED device is that it requires a reflector as such, that is, the light source is a complete optical system of the designed device, which fully ensures the regulated light distribution of the lamp. The purpose of this work is an unbiased comparative study of the applicability of these engineering approaches in the development of modern lighting devices, which will have practical value for developers of lighting systems. An impartial and thorough analysis of the application of these approaches in the design of optoelectronic devices was performed, and the advantages and disadvantages of such design for both the manufacturer and the consumer were consistently considered. The main advantage of designing luminaires with discharge lamps is the comprehensive development of devices, storage of proprietary technologies and engineering and design developments, and independence from foreign suppliers of components, the main advantages of LED-based devices are that new developments meet modern requirements for energy efficiency and environmental friendliness.
Keywords: Luminous Intensity Curve; Reflector; Industrial Lighting; LED Modules; Discharge Lamps; Energy Efficiency; Light Output